La recherche des champignons marins actifs contre quelques bactéries pathogènes - Mansouri, Nabaouiya Ikram; Ben_nouna, Nadjet (My University, 2024)
Marine fungi research has been of great interest to the scientific community for many years, with many studies carried out in various regions of the world and on different substrates. In this work, we explored the fungal diversity present in the coastal areas of Mostaganem, Algeria, by collecting samples of sand and algae from several sites: Hadjadj, Cap Ivi, Salamandre, Sablette and Sidi El Majdoub. The samples were taken for 4 months from February to May 2024. This study aimed to isolate and identify marine fungi potentially active against bacterial pathogens. Macroscopic and microscopic analysis of isolates revealed the presence of several fungal species, totaling 25 strains identified. Among these, Penicillium spp. (40%) was the most predominant, followed by Aspergillus (16%), yeasts (16%), sterile mycelium fungi (16%), Mucor (8%) and Stachybotrys (4%). Antagonistic activity of the strains against pathogenic bacteria revealed that Aspergillus terreus, isolated from the green alga Ulva lactuca, was particularly effective against Escherichia coli and Aeromonas hydrophila, with interesting inhibition zones of 25.58 mm and 28.97 mm respectively. In addition, Enzyme activity tests showed that some strains possessed notable amylase and protease activities. These results show that marine fungi are promising sources of novel antimicrobial agents and other metabolites, offering a solution against antibiotic resistance and other biotechnological solutions. Future research will focus on the purification, optimization and exploration of fung therapeutic potential, opening new avenues in the exploitation of marine fungi in the therapeutic and industrial fields.
Keywords: marine fungi; Aspergillus terreus; bioactive metabolites; antibiotic resistance; Ulva lactuca; Escherichia coli; Aeromonas hydrophila